2019
DOI: 10.1038/s41438-019-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and standardization of transient expression assays for gene functional analyses in strawberry fruits

Abstract: Strawberry is increasingly used as a model plant for research on fruit growth and development. The transient gene manipulation (TGM) technique is widely used to determine the function of plant genes, including those in strawberry fruits. However, its reliable application for the precise identification of gene function has been difficult owing to the lack of conditional optimization. In this study, we found that successful transient gene manipulation requires optimization, with the vector type, temperature, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
0
32
0
2
Order By: Relevance
“…Indeed Agrobacterium can be perceived as a pathogen by the fruit and stimulate similar responses as C. acutatum , including those leading to FaRALF3 expression. The variability affecting strawberry Agrobacterium -mediated transformation depending on technical and environmental conditions has recently been described [64]. It was shown that the expression level of a reporter gene is normally distributed in an population of 30 treated fruits, with huge variation among different fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed Agrobacterium can be perceived as a pathogen by the fruit and stimulate similar responses as C. acutatum , including those leading to FaRALF3 expression. The variability affecting strawberry Agrobacterium -mediated transformation depending on technical and environmental conditions has recently been described [64]. It was shown that the expression level of a reporter gene is normally distributed in an population of 30 treated fruits, with huge variation among different fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed Agrobacterium can be perceived as a pathogen by the fruit and stimulate similar responses as C. acutatum, including those leading to FanRALF3 expression. The variability affecting strawberry Agrobacterium-mediated transformation depending on technical and environmental conditions has recently been described [76]. It was shown that the expression level of a reporter gene is normally distributed in a population of 30 treated fruits, with huge variation among different fruits.…”
Section: Fveralf3 Promoter-reporter Assaymentioning
confidence: 99%
“…Strawberry (Fragaria), as a distinct member of Rosaceae, is not only an important fruit crop worldwidely, but is also regarded as a model for studying non-climacteric fruit ripening [1]. In the past years, a large of genes related to strawberry fruit ripening have been identi ed via traditional stable and transient transgenic systems in strawberry; however, more or less, the limitation is existed [2][3][4]. Thus, development of a rapid, e cient, and stable transformation system is required for strawberry research and breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Such as, it takes at least 15 months from transformation to gaining transgenic fruits for gene function analysis in ripening [17,18]. In addition, although the transient transformation technology in strawberry fruits provides a rapid tool to study gene function in ripening, some limits are existent in fruit transient transgenic system [2,4].…”
Section: Introductionmentioning
confidence: 99%